Can photodynamic therapy be an alternative method in melanoma treatment? - Wawrzuta, Anna; Saczko, Jolanta; Kulbacka, Julita; Chwiłkowska, Agnieszka (Dermatology Review/Przegląd Dermatologiczny, 2009)
Melanoma is the most severe of all skin neoplasms as it may grow rapidly and metastasize. The application of photodynamic therapy (PDT) opens new perspectives in treatment of this tumour. Photodynamic therapy is an effective local cancer treatment that induces cytotoxicity through intercellular generation of reactive oxygen species. The disintegration of cellular structures and modulation of genetic information induced by PDT direct cancer cells to a death pathway. Numerous studies suggest that the exposure of tumour cells to PDT can lead to cell death via two separate processes: apoptosis or necrosis. In contrast to necrosis, apoptosis is an energy dependent, distinct form of cell death that follows a sequence of genetically programmed events and proceeds without inflammation. This study presents the mechanism of photodynamic therapy and its potential in melanoma treatment.